Migrating Giant Honey Bees (Apis dorsata) Congregate Annually at Stopover Site in Thailand - Robinson, Willard S. (PLOS ONE, 2012)
Giant honey bees (Apis dorsata) of southern Asia are vital honey producers and pollinators of cultivated crops and wild plants. They are known to migrate seasonally up to 200 km. It has been assumed their migrations occur stepwise, with stops for rest and foraging, but bivouacking bees have rarely been seen by scientists. Here I report discovery of a site in northern Thailand where bivouacs appeared in large congregations during the wet seasons of 2009 and 2010. The bivouac congregation stopover site is a small mango orchard along the Pai River. Bivouacs rested in branches of mango and other tree species in the immediate vicinity. Departures were preceded by dances indicating approximate direction and apparently, distance of flights. Such consistent stopover sites likely occur throughout southern Asia and may support critical, vulnerable stages in the life history of giant honey bees that must be conserved for populations of the species to survive.